2014
DOI: 10.1007/s00702-014-1190-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of cigarette smoking in the limbic system revealed by 3 tesla magnetic resonance spectroscopy

Abstract: Several studies and recent models of effects of nicotine, the main addictive and psychoactive component in tobacco, point to action of the drug on the limbic system during maintenance of addiction, either direct or indirect via projections from the ventral tegmental area. The objective of this study was to demonstrate physiological effects of cigarette smoking on the hippocampus and the grey matter of the dorsal anterior cingulate cortex in the human brain with regard to addiction and withdrawal. This aim was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
3
22
1
Order By: Relevance
“…Relative to healthy subjects, cultured macrophages from tobacco smokers exhibit diminished proinflammatory cytokine secretion after incubation with LPS, while anti-inflammatory cytokine secretion was unaffected [114-116]. However, there is considerable evidence opposing this working hypothesis [103, 104, 107, 117, 118]. Future research is needed to parse these relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to healthy subjects, cultured macrophages from tobacco smokers exhibit diminished proinflammatory cytokine secretion after incubation with LPS, while anti-inflammatory cytokine secretion was unaffected [114-116]. However, there is considerable evidence opposing this working hypothesis [103, 104, 107, 117, 118]. Future research is needed to parse these relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Each study imaged individuals without requiring smoking abstinence prior to scanning [103-105]. Two MRS studies found no difference in myo- inositol levels between tobacco smokers versus healthy controls across brain regions [103, 104], while the third found myo- inositol levels were significantly lower by ~12% among tobacco smokers relative to healthy controls in the dorsolateral prefrontal cortex, but not the anterior cingulate cortex (ACC) [105]. However, in that study, smokers reported more frequent alcohol use than controls, which may have contributed to these findings [105].…”
Section: Resultsmentioning
confidence: 99%
“…Although the specific mechanisms underlying the neurocognitive effects of smoking are not yet fully elucidated, possibilities include altered brain structure, connectivity, receptor binding, hypoxic events, and/or alterations in biochemistry and neurotransmission (Durazzo et al, 2010;Mennecke et al, 2014;O'Neill et al, 2014). Although acute nicotine administration may lead to some cognitive performance improvement in short-term abstinent smokers (Rose, Behm, & Westman, 2001), over time, neural-structural changes in chronic smokers include loss of prefrontal cortical and cerebellar gray matter and reduced anterior cingulate size when comparing chronic smokers with nicotine-naïve alcoholic patients (Durazzo, Gazdzinski, & Meyerhoff, 2007).…”
Section: Smoking → Executive Functioning (Path A)mentioning
confidence: 99%
“…Chronic cigarette smoking desensitize and upregulate the nicotinic acetylcholine receptors, which then stimulate various neurotransmitter systems, including acetylcholine, dopamine, glutamate (excitatory) and gamma amino butyric acid (GABA; inhibitory) [21]. Studies on smokers have indicated the role of glutamate and GABA, in both the reinforcing effects of nicotine and the development of nicotine dependence [25].…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI (fMRI) studies have revealed that chronic smoking alters the brain activity in regions involved in attention, working memory processes, higher order cognitive processing, anxiety and reward processing [14][15][16][17][18][19]. Proton magnetic resonance spectroscopy (MRS) studies on smoking have demonstrated metabolic alterations in N-acetyl aspartate (neuronal marker) and glutamate (excitatory neurotransmitter) levels in brain regions associated with reward circuitry, namely, the anterior cingulate cortex, the dorsolateral PFC, the thalamus, and the hippocampus [20][21][22]. Although most of these studies raised "sex-specific effects of nicotine addiction" as a topic for future investigations, this question still remains unaddressed.…”
Section: Introductionmentioning
confidence: 99%